THE SPELLING ENGLISH SOUNDS FACED DIFFICULTY BY THE EIGHTH SEMESTER STUDENTS OF SMP NEGERI 2 RANTEPAO - daniel M.R paembonan (UKI TORAJA, 2016)
Daniel Paembonan. 2016. The Spelling English Sounds Faced Difficulty by theEighth Semester Students of SMP Negeri 2 RantepaoThe objective of the study is to find out the spelling difficulty faced by the eighthsemester students of SMP Negeri 2 Rantepao.In order to achieve the objective of this study, the writer designed this experimentby descriptive method using written test and questionnaire. The tests were used tofind out the spelling difficulty faced by the eighth semester students of SMPNegeri 2 Rantepao.The result of the research showed that the students were difficult to spell English(vowel and consonant) sound, but they were more difficult to spell the vowel thanconsonant sound. It was proved by the of mean score in vowel sound 2, 77(categorized as very poor) and 4, 54 in consonant sound (categorized as poor).And it was caused the students were difficult to differentiating the English sound,(special for the same sound [?, ð]), students were lazy to learn the Englishphonetic, less self confidence to pronounce the English sound, less comprehendthe material, and less book in the library and the lecturer’s method didn’tavailable with the material.Basedon the data analisys found out that the spelling difficulty faced by the eighthsemester students of SMP Nigeria 2 Rantepao are commonly consonants sound